A new dichromatic species of Oaxacanthaxia Bellamy 1991 (Coleoptera: Buprestidae) from Quintana Roo, México - Bellamy, C. L. (Zootaxa, 2011)
x Twenty years ago, a new buprestid genus and species, Oaxacanthaxia viridis Bellamy 1991 was described for specimens collected by Jim Cope during the summer of 1989 in the Isthmus of Tehuantepec, Oaxaca, México (Bellamy 1991). The summer following that publication (1992), a group of 10 buprestiphiles from Australia, Czech Republic, Germany, the United States and Russia combined forces to collect in southern México (Guerrerro and Oaxaca), hoping to find, among many other taxa, O. viridis. That quest was partly successful (only one female specimen collected by Dave Verity), but completely unexpectedly Ted MacRae, Gayle Nelson and Dave Verity collected a second species of Oaxacanthaxia, which was described as O. nigroaenea by Nelson & MacRae (1994). Twelve years later, Niehuis & Gottwald (2006) described a new species from Nicaragua: O. vandenberghei, named for Manfred Niehuis’ nephew Eric van den Berghe, who had lived and collected for several years in Nicaragua. Most recently Hornburg & Gottwald (2008) described O. aenea from Venezuela, greatly expanding the range of the genus.